Importance of a Coastal Artificial Lake in Methylmercury Production: A Case Study of Lake Changpo, Korea - Kundu, Sampa Rani; Kim, Eunhee; Han, Seunghee; Lee, Byeong-Gweon (Ocean science journal, 2019)
Lake Changpo (LC) is an artificial freshwater lake surrounded by wetlands and farmlands, inundated with water during the wet season, on the southwest coast of Korea. To investigate the temporal and spatial distribution of total mercury (THg) and methylmercury (MeHg) in LC and adjacent Cheonggye Bay (CB), water and sediment samples were collected five times from August 2009 to August 2010. In addition, fish samples were collected to examine Hg levels. The THg concentration in the unfiltered water of LC ranged from 1.6 to 5.0 ng/L and had a positive relationship with total suspended solids (TSS). This positive relation indicates that TSS is an important source of THg in LC. The MeHg levels were highest during August and ranged from 0.03 to 0.19 ng/L in unfiltered water and from 0.01 to 0.10 ng/L in filtered water. Both the THg and MeHg levels in the sediments were significantly correlated with the organic matter content of the sediments. Overlapping of the spatial and temporal distribution patterns of MeHg and %MeHg between the water column and sediments suggests that production and diffusion of MeHg from the sediment, particularly during warm summer, was the primary source of MeHg in the water column. In addition, higher THg and MeHg concentrations were found in catfish, a bottom-dweller fish. Thus, the higher THg and MeHg concentrations in LC compared to CB demonstrate that artificial lakes could be a significant site for Hg methylation and an additional source of MeHg to coastal seas.